AVRUPA BİRLİĞİ’NE KATILMA YOLUNDA BULGARİSTAN, ROMANYA VE TÜRKİYE : KOMİSYONUN 2003 İLERLEME RAPORLARI IŞIĞINDA BİR KARŞILAŞTIRMA* - Ercüment Tezcan (Ankara Avrupa Çalışmaları Dergisi)
1998 the Commission regularly publishes reports on the countries candidate for accession to the European Union. From Regular Progress reports of 2003 by the Commission on Bulgaria, Romania and Turkey, it arises clearly that Bulgaria and Romania fulfill the Copenhague criteria. With these two countries the negotiations officially began on February 15, 2000. Bulgaria, and Romania will become members of the Union in 2007. Turkey does not yet satisfy these criteria. In December 2004 things will be clearerfor Turkey.Doğu Blokunun 1990’h yılların başında yıkılması, Avrupa Birliğinin şu ya da bu biçimde genişlemesi sorununu gündeme getirmiştir.